1939
DOI: 10.1017/s000748530000465x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Physical Ecology of Tortrix postvittana, Walk. (Lep.)

Abstract: 1. The thermal constant and the zero of the velocity curve have been determined for each of the pre-adult stages of Tortrix postvittana, Walk. The experimental methods are described. The thermal constant for the eggs is 153 day degrees C. and the zero of the velocity curve 4·80°C. The corresponding constants for the larvae are 469 day degrees C. and 8·05°C, and for the pupae 182 day degrees C. and 5·93°C.2. The experimentally determined constants and the mean monthly temperatures have been used to calculate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Most trapping systems for Lepidoptera are baited with the female sex pheromone, and therefore are limited to sampling male moths. However, baits to attract female Lepidoptera do exist, and include crude fermentation or other baits (Dumbleton 1939; El‐Sayed et al. 2005), refined baits based on semiochemicals (Light et al.…”
Section: Tools and Methods To Measure Predict And Enhance Moth Qualitymentioning
confidence: 99%
“…Most trapping systems for Lepidoptera are baited with the female sex pheromone, and therefore are limited to sampling male moths. However, baits to attract female Lepidoptera do exist, and include crude fermentation or other baits (Dumbleton 1939; El‐Sayed et al. 2005), refined baits based on semiochemicals (Light et al.…”
Section: Tools and Methods To Measure Predict And Enhance Moth Qualitymentioning
confidence: 99%
“…On the meridic diet with and without mould inhibitor, the average numbers of eggs laid per female were 598 and 502 respectively. Dumbleton (1932) recorded larval and pupal periods of 42 and 14 days respectively on apple, at an average temperature of 20° C. Dumbleton (1932Dumbleton ( , 1939 also reported a considerable variation in the length of developmental period of individuals in any one generation, and noted that different generations overlap to a great extent. This view was supported by Thomas (1965 in spite of the controlled conditions of environment and nutrition, a similar pattern is evident; for example, the ranges of larval periods for males and females were 19-42 days and 22-49 days respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Dumbleton (1932) reported that a female deposits an average of 100 eggs on apple; Thomas (1965) obtained an egg count of 856 for an oligidic diet based on sheep nuts. On the meridic diet with and without mould inhibitor, the average numbers of eggs laid per female were 598 and 502 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Species of Australoglypta Gauld are known only from Australia and Papua New Guinea (Gauld 1984a), with this species recorded from Bundoora, Warrandyte and Studley Park in Victoria (ANIC, VDAM) and Coonawarra in South Australia (WINC). There is a description of an unidentified species of 'Glypta' reared from E. postvittana from Tasmania (Dumbleton 1939), which is probably this species. However, we have been unable to locate any voucher material to confirm this.…”
Section: Family Ichneumonidaementioning
confidence: 99%